Pengaruh Kadmium Terhadap Struktur Histologis Insang Ikan Lele (Clarias Batrachus) - Hayati, Alfiah (Jurnal Matematika dan Ilmu Pengetahuan Alam, 2015)
This study determined the effect of cadmium (Cd) on the structure of the gills of catfish (Clarias batrachus). Animals were exposed to 0 (control), 1, 2, and 4 ppm of Cd during 14 days. The results showed that Cd affected the structure of the gills of catfish, such as edema, hyperplasia, and fusion gill lamela. The gills of control animals showed the lowest damage (13.9%), where as the level of gill damage of fish exposed to 1, 2, and 4 ppm were 45.7; 71.6; and 82.1% respectively.Keywords: cadmium, catfish, edema, hyperplasia, gills.